Cathepsin H and cathepsin B of Cynoglossus semilaevis are involved in anti-bacterial immunity against Edwardsiella tarda. Issue 134 (March 2023) - Wang, Yilong; Xu, Hang; Sun, Boguang
Abstract: Cathepsin H and Cathepsin B are two lysosomal cysteine proteases participating in various physiological processes including immune responses. In fish, the functional roles of Cathepsin H and Cathepsin B during bacterial infection are less understood. In a previous work, we characterized a Cathepsin B homologue (CsCatB) of half-smooth tongue sole ( Cynoglossus semilaevis ), an economically valuable fish species in China. In this report, we identified a Cathepsin H homologue (CsCatH) from C. semilaevis . In healthy tongue sole, the transcriptional expression of CsCatH was detected in nine different tissues. Laser scanning confocal microscopic analysis showed that ectopically expressed CsCatH and CsCatB were co-localized with the lysosome. Upon infection by Edwardsiella tarda, a significant fish pathogen which caused a severe fish disease termed edwardsiellosis, the expressions of CsCatH and CsCatB were remarkedly upregulated. The knockdown of CsCatH and CsCatB significantly increased the replication of E. tarda and mitigated E. tarda -induced apoptosis in tongue sole tissues. These findings revealed the importance of CsCatH and CsCatB in anti-bacterial immunity of tongue sole. Highlights: A cathepsin H homologue, CsCatH, was identified from Cynoglossus semilaevis. The mRNA of CsCatH was detected in nine tissues of C. semilaevis. The expressions of CsCatH and CsCatB were induced by Edwardsiella tarda infection. RNAi of CsCatH or CsCatB led to enhanced bacterial dissemination. RNAi of CsCatH or CsCatB led to reduced apoptosis upon E. tarda infection.